Experimental research of the Plasma Arc Cutting Process - Lazarevic, Andjela (Journal of Applied Engineering Science, 2014)
The results of the experimental research of plasma cutting process were presented in this paper. The impact analysis of the input process parameters: cutting current (I), cutting speed (v) and material thickness (s), on the output process parameters: kerf (sr), surface roughness (RZ) and bevel angle (b) was done. The plasma cutting machine (CNC) – type HPm Steel Max 6.25 was used in combination with the plasma cutting unit – type Hypertherm HPR130. The workpiece material was stainless steel X10CrNiMn-16-10-2 (EN 10025). Large numbers of cuts were made using the different machine and plasma cutting unit settings. After process data collection, its analysis was done by the software application MatLab. The results were presented in tables as well as on diagrams, showing particularly dependencies between input and output parameters under various conditions. The objective of this paper was to visualize the influence of input parameters on the output parameters, and to prepare the data for plasma cutting process modelling, using different methods: statistical and artificial intelligence.